Investigating the impact of a falls prevention community of practice in a residential aged-care setting: A mixed methods study protocol - Francis-Coad, J.; Etherton-Beer, C.; Bulsara, C.; Nobre, D.; Hill, Anne-Marie (2015)
© 2015 John Wiley & Sons Ltd. Aim: The aim of this study was to facilitate the implementation and operation of a falls prevention Community of Practice in a residential aged-care organization and evaluate its effect on falls outcomes. Background: Falls are a substantial concern across the residential aged-care sector with half its older population falling annually. Preventing falls requires tailoring of current evidence for reducing falls and adoption into daily activity, which is challenging for diversely skilled staff caring for a frailer population. Forming a community of practice could provide staff with the opportunity to share and develop their expertise in falls prevention and innovate change. Design: A mixed methods design based on a realist approach conducted across 13 residential care facilities (N = 779 beds). Method: Staff will be invited to become a member of the community of practice with all sites represented. The community of practice will be supported to audit falls prevention activity and identify gaps in practice for intervention. The impact of the community of practice will be evaluated at three levels: individual member level, facility level and organizational level. A pre-post design using a range of standardized measures supported by audits, surveys, focus groups and interviews will determine its effect on falls prevention practice. Falls outcomes will be compared at five time intervals using negative binomial regression and logistic regression. The study is funded 2013-2017. Conclusion: Findings from this research will assist residential aged-care providers to understand how to effectively translate evidence about falls prevention into clinical practice.